Career Preparedness: The role of Experience before a PhD - Cadilhe, Maria; Almeida, Betariz; Rodrigues, Ana I.; Santos, Marta (ICAReAlumni Conference Proceedings, 2023)
OECD wide the number of PhD holders has been growing every year, but job opportunities in the Higher Education Sector, as their privileged employer, do not seem to keep up with PhD holders’ numbers [...]